2000
DOI: 10.1162/105474600566952
|View full text |Cite
|
Sign up to set email alerts
|

Duration and Exposure to Virtual Environments: Sickness Curves During and Across Sessions

Abstract: Although simulator sickness is known to increase with protracted exposure and to diminish with repeated sessions, limited systematic research has been performed in these areas. This study reviewed the few studies with sufficient information available to determine the effect that exposure duration and repeated exposure have on motion sickness. This evaluation confirmed that longer exposures produce more symptoms and that total sickness subsides over repeated exposures. Additional evaluation was performed to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
144
2
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(175 citation statements)
references
References 15 publications
13
144
2
3
Order By: Relevance
“…Future protocols should implement a short familiarization session that includes braking behavior, in order to identify participants who are more prone to feel simulator sickness symptoms when experiencing longer exposure. Because our results clearly show that repeated exposures reduce simulator sickness symptoms, as has been reported earlier 45 . A stepby-step training should be implemented for those participants who are more susceptible to feel pronounced discomfort to longer experimental runs.…”
Section: Prevention Of Simulator Sicknesssupporting
confidence: 90%
See 1 more Smart Citation
“…Future protocols should implement a short familiarization session that includes braking behavior, in order to identify participants who are more prone to feel simulator sickness symptoms when experiencing longer exposure. Because our results clearly show that repeated exposures reduce simulator sickness symptoms, as has been reported earlier 45 . A stepby-step training should be implemented for those participants who are more susceptible to feel pronounced discomfort to longer experimental runs.…”
Section: Prevention Of Simulator Sicknesssupporting
confidence: 90%
“…In addition, before each session, participants were asked if they were in their usual state of fitness (that is, not suffering from a cold or flu, hangover, etc.). Although several strategies were used to reduced simulator sickness incidence, the long exposure to simulated environment used to evaluate multiple driving behaviors increases the chance of severe discomfort 45 . Therefore, new protocols should be developed to reduce simulator sickness symptoms and to identify participants who will be more prone to be simulator sick.…”
Section: Prevention Of Simulator Sicknessmentioning
confidence: 99%
“…This occurs more commonly in more experienced drivers and in people who have not regularly played computer and video games (Kulisevsky & Pagonabarraga, 2009). The drop out due to motion sickness experienced in this study (25%) was within the range reported by other studies using driving simulators, from 9% (Lee, et al, 2003) to 57% (Kennedy & Fowlkes, 2000), with older drivers being more susceptible to motion sickness. Kulisevsky and Pagonabarraga (2009) found that participants who experienced motion sickness in simulated driving did not have a reduced performance during on-road assessment and suggested that incidence of motion sickness is related to factors other than driving ability.…”
Section: Motion Sicknesssupporting
confidence: 69%
“…It was noted that both of these participants later experienced motion sickness and withdrew from the study. Kennedy and Fowlkes (2000) found that increased exposure to simulated environments might increase the rate of motion sickness-related participant dropouts. Although this study cannot comment upon this phenomenon, additional research into a possible correlation of exposure time to motion sickness would be useful to provide guidelines for simulator scenario design, especially for older adults or people with PD.…”
Section: Driving Simulator Data 431 Length Of Simulator Practice Timementioning
confidence: 99%
“…The acclimation drive was a scripted, constrained drive aimed to allow the participant to become accustomed to simulator driving and to help prevent simulator sickness, as suggested by Kennedy (Kennedy, Stanney & Dunlap, 2000). The drive started in an urban location containing several obstacles around which the user was forced to navigate.…”
Section: Taskmentioning
confidence: 99%